Młodzież w obszarze mediów lokalnych w Polsce i na Łotwie - Roguska , Agnieszka (Studia Edukacyjne, 2020)
The article is aimed to present scientific results based on young people’s activity in local media. It becomes even more interesting as the young generation is growing up in the era of global expansion, including media of a wide range scale of influence. This makes it even more interesting to trace how young people in Poland and Latvia understand local media. The research was carried out during three visits to Latvia: twice during an internship at Daugavpils University in 2014 and then at Riga Teacher Training and Educational Management Academy in 2015 and during the Erasmus + Project at Riga Teacher Training and Educational Management Academy in 2015. In the same period, similar studies were conducted at the Department of Humanities at Siedlce University of Science and Humanities. The study comprised a group of 160 young Polish and 108 Latvian university students aged 20-26 and was based on a diagnostic survey method. A survey and a questionnaire survey were used as tools, supported by interviews based on previously prepared tasks. The article discusses issues such as the need for local media functioning, the respondents’ most frequently used media and the young people’s participation in creating the content and the image of local media.